The Holy Trinity: Between Mystery and Analysis. (3rd September 2018) - Patterson, Colin
Abstract: Two significant strands of trinitarian theology, the analytic and the apophatic, emphasize considerations of logical consistency and divine incomprehensibility respectively. This article seeks to mediate between these two seemingly opposed lines of thought by arguing for a fuller awareness of the particular mystery associated with the trinitarian notion of 'person'. By specifying more closely this mystery of divine personhood, I qualify an overzealous apophaticism and also open up some scope for analytic approaches. I then highlight an implication of the mystery of divine personhood that any proposition linking together person‐language and nature‐language (e.g. 'the Son is God') necessarily contains its own mystery and cannot be understood in analytic terms.